Leonee Ormond (ed.), The Reception of Alfred Tennyson in Europe. London and New York: Bloomsbury, 2017. Pp. 424. - Ekdawi, Sarah (Σύγκριση/Comparaison/Comparison, 2018)
Δε διατίθεται περίληψη / no abstract available